SIDOLA: SISTEM IOT PENGUNCI PINTU LAB ELEKTRONIKA UNJ BERBASIS ESP32 - Yusuf Syani (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2026)
The Electronics Laboratory at Universitas Negeri Jakarta (UNJ) frequently encounters door security risks, particularly during campus power outages or outside operational hours, potentially leading to unauthorized access and the theft of expensive equipment. This study develops SIDOLA (ESP32-Based IoT Door Lock System for UNJ Electronics Laboratory) as an innovative solution that integrates remote control capabilities via a mobile/web application, a backup power supply, and automated voice notifications synchronized with the academic schedule. The primary objective is to design, develop, and validate the SIDOLA prototype to achieve a Technology Readiness Level (TRL) of 4. Specifically, this research aims to: (1) analyze the laboratory's security requirements; (2) design the hardware and software architecture utilizing an ESP32, a solenoid lock, a speaker, and backup power; (3) develop a prototype integrating IoT and cybersecurity features; and (4) conduct functional testing and expert validation. This study employs the Research and Development (R&D) method, adopting Sugiyono's simplified version of the Borg and Gall model, which consists of four stages: Needs Analysis, Design, Product Development, and Testing. The novelty of SIDOLA lies in its specific adaptation for educational laboratory environments, featuring voice notifications based on the UNJ academic schedule, resilience to campus power outages, and potential integration with student RFID systems and the laboratory management system of the Faculty of Engineering (FT) UNJ. This research aligns with the UNJ Research Master Plan (RIP) 2021-2025 (under the themes of Science and Technology, and Educational Technology) and contributes to Sustainable Development Goal (SDG) 9 by strengthening a resilient and scalable laboratory infrastructure applicable to all laboratories within the Faculty of Engineering. The targeted outputs of this research include a working prototype, Intellectual Property Rights (IPR), a publication in a SINTA-indexed journal, a research poster, mass media publications, and a research video. Ultimately, the findings are expected to enhance the security of laboratory assets and improve the management efficiency of educational facilities at UNJ.